Fuzzy Decision Trees as a Decision Making Framework in the Private Sector - Vijaya, M; Arthi, M (International Journal of Computer Sciences and Engineering, 2025)
Systematic approaches to making decisions in the private sector are becoming very common. Most often, these approaches concern expert decision models. The expansion of the idea of the development of e-participation and e-democracy was influenced by the development of technology. The solution presented in this papers concerns fuzzy decision making framework. This framework combines the advantages of the introduction of the decision making problem in a tree structure and the possibilities offered by the flexibility of the fuzzy approach. The possibilities of implementation of the framework in practice are introduced by case studies of investment projects appraisal in a community and assessment of efficiency and effectiveness of private sector